2019
DOI: 10.3390/su11030853
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Evaluating the Business Analytics Maturity of University Programmes

Abstract: The impact that business analytics (BA) has on companies’ performance will cause, in the near future, a significant increase in the demand for specialists in the field. Universities will play an important role in covering the deficit of professionals already reported by companies, provided that their offer is tailored to real market demands and their students are prepared to acquire the appropriate knowledge and skills. This paper proposes a framework for assessing the maturity level of BA in economic universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…According to Muntean et al (2011), using business intelligence for decision support in university administration is one method to see business intelligence in the context of the educational environment in business operations carried out in higher education institutions. He underlined that while using business information in this manner, a set of relevant criteria should be employed, and that identifying and monitoring key performance criteria is critical for university management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Muntean et al (2011), using business intelligence for decision support in university administration is one method to see business intelligence in the context of the educational environment in business operations carried out in higher education institutions. He underlined that while using business information in this manner, a set of relevant criteria should be employed, and that identifying and monitoring key performance criteria is critical for university management.…”
Section: Discussionmentioning
confidence: 99%
“…When looking at the literature on business intelligence technology and higher education institutions, the fol-lowing topics come up: its applications (Hamad, 2021), improve performance in higher education (Abduldaem & Gravell, 2021), model to evaluate some national higher education (Khatibi et al, 2020;Ülker & Coşkun, 2021), analyzing educational data (Villegas-Ch et al, 2020), data and information for student admission process (Mirwansyah & Sari, 2021), governance framework in a university (Niño et al, 2020), quality management of higher education institutions (Pérez -Pérez, et al, 2018), performance measurement (Vallurupalli & Bose, 2018), course management systems (Van Dyk & Conradie, 2007), providing a framework and component dedicated for university's management (Muntean et al, 2011). Higher education and business intelligence studies have been conducted in a variety of disciplines, as may be shown.…”
Section: Business Intelligence (Bi) and Higher Educationmentioning
confidence: 99%
“…The study claimed that business intelligence is a very useful tool for the university decision support system (DSS). Further research enquiry into the importance of business intelligence (Muntean, Bologa, Corbea, & Bologa, 2019), went further to determine how business intelligence systems affect or support the university strategy. Thus, the aim of the paper is to determine how a university can use business intelligence to assess an e-learning platform.…”
Section: Business Intelligence and University Success And Sustainabilitymentioning
confidence: 99%
“…The reported benefits of BIS from these studies include providing faster and more accurate reporting, an improved decision-making process, improved customer satisfaction, increased revenues, savings in IT resources required, and lastly, an improved communication within the company (Hocevar & Jaklic, 2010). Muntean, Bologa, Bologa, & Florea (2011) emphasized that most of the applications of BI in the context of the educational environment is using it for decision support of universities' management. Similarly, Kabakchieva (2015) asserted that a lot of the university's BI initiatives are focused on three main areas which include: supporting administrative and management activities, academic issues and university relations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, Durso (2009) also reported of BIS being used in some American universities to analyze add/drop information and class failure patterns to identify the potential students who are at risk of dropping and then direct them to student support services. Again, Muntean et al (2011) proposed a framework for developing a BI solution for universities. Their study also presented how a university can use BI to assess an e-learning platform.…”
Section: Application Of Bi Tools and Technologies In Heismentioning
confidence: 99%